Pengaruh Penggunaan E-Money dan Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi Universitas Jember - Nurus Shofa Septi Ningrum; Riyanto Efendi; Astrian; Choirul Hudha; Vicky (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The development of digital financial technology, particularly electronic money (e-money), has made transactions easier. However, this convenience also has the potential to increase consumptive behavior, especially among students. Students often buy things simply because they want them, so it is hoped that students can control themselves in order to prioritize their needs over their wants. This study aims to evaluate the impact of electronic money usage and personal regulation on the consumption patterns of students in the Economics Education Study Program at the University of Jember. The research focuses on the role of non-cash transactions and personal capacity in limiting students' impulse buying. The evaluation method used is multiple linear regression analysis with the support of SPSS software version 23. The research findings reveal that: (1) the use of electronic money does not have a significant effect on student consumption patterns; (2) personal regulation also does not show a significant impact when tested separately; and (3) when both factors are analyzed together, they are proven to significantly influence consumption patterns with a significance level of 0.025 and a coefficient of determination of 0.073. These results indicate that electronic money and personal regulation only contribute about 7.3% to shaping student consumption patterns, while the remaining 92.7% is influenced by external variables that were not investigated in this study